Over a million students use our free study notes to help them with their homework
First we must expand the demoninator to; (x+3)(x-3)Then we can multiply the left hand fraction on top and bottom by (x-3) to get a common demoninatorthis gives us; (4x)/((x+3)(x-3)) - ((2)(x-3))/((x+3)(x-...
There are 2 ways to solve this equation:Method 1:Expand the brackets by multiplying everything inside the brackets by 4 to make 4x-20=18Then +20 to both sides making 4x=38Then divide by 4 to find x, there...
The important point in the question is the term 'stationary point'. This is where the graph of y will 'flattern out'. If we look at this graph, we can say that the gradient is equal to 0 at this point. Th...
First take (x+2)(x+3) and expand to get x2 +3x+2x+6, which can be simplified to equal x2+5x+6.Then mutiple x2+5x+6 by (x+5). This will give you x3+5x2Answered by Cora H. • Maths tutor2904 Views
Use cos(A+B)=cosAcosB-sinAsinB and let A=B so cos(A+A)=cosAcosA-sinAsinA this means cos(2A)=cos2A-sin2A and since cos2A+sin2A=1, cos2A=1-sin2Answered by Rebecca F. • Maths tutor18735 Views
←
595
596
597
598
599
→
Internet Safety
Payment Security
Cyber
Essentials